Two new earthworm species (Oligochaeta: Annelida) of the Caribbean region of Colombia - Celis, Liliana V.; Rangel-Ch, Orlando (Zootaxa, 2015)
Two new earthworm species are described, Periscolex malibu sp. nov. (Rhinodrilidae) and Righiodrilus lebrijae sp. nov. (Glossoscolecidae). They were found in relicts of tropical dry forests surrounding wetlands in the southern department of Cesar, located near the Caribbean coast of Colombia. Periscolex malibu sp. nov. is close to P. fuhrmanni Michaelsen, 1913 by the position of both clitellum and tubercula pubertatis, but differs in the extension of the clitellum and in the presence of five pairs of spermathecae. Righiodrilus lebrijae sp. nov is close to R. paolettii Righi, 1984a by the extension of the clitellum, but differs in the extension of the tubercula pubertatis, the extension of the seminal vesicles, the position of the male pores, the arrangements of setae, and the shape of the spermathecae.